Multi-mode hydrogen storage in nanocontainers - Shervani, Suboohi; Mukherjee, Puspal; Gupta, Anshul; Mishra, Gargi; Illath, Kavya; Ajithkumar, Thallaseril G.; Sivakumar, Sri; Sen, Pratik; Balani, Kantesh; Subramaniam, Anandh (International Journal of Hydrogen Energy, 2017)
Hydrogen can be stored in containers or in materials (in molecular or atomic forms). The atomic form can further exist as multiple phases. Molecular hydrogen can be adsorbed on the surface or can be present inside the material. By invoking multiple modes of hydrogen storage, we establish a paradigm shift in the philosophy of hydrogen storage. Using a novel strategy of storage of molecular hydrogen in metal (Pd) nanocontainers, we observe that 18% hydrogen is in molecular form. Interestingly, this is achieved at 25 °C and 1 atm pressure; which is in contrast to storage in MOFs and carbonaceous materials like nanotubes. Enhancement in storage capacity as compared to Pd nanocrystals of the same mass is observed (36% increase at 1 atm & 25 °C), along with fast kinetics (0.5 wt% hydrogen absorption in 5 s). A new mechanism for hydrogen storage involving the dual catalytic role of Pd is established.